PENGARUH MANAJEMEN SISTEM INFORMASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN BURU SELATAN - LAITUPA, AISA (Patria Artha University, 2021)
The study aims to analyze the effect of management information systems (SIM) on employee performance at the Office of KOMINFO, South Buru Regency.Causional research uses a quantitative approach with the independent variable and the dependent variable where the independent variable is the management information system (X) with indicators: SIM helps in decision making, SIM supports the planning function, SIM provides complete and timely information, SIM as a determination work program. And the dependent variable is employee performance (Y), with indicators: Quality, which is related to the suitability of the results desired, Quantity is the amount produced either in the form of value for money, number of units, or number of activity circles, Timeliness is compliance with the standards a work implementation organization that can be completed within a specified time has been established, Attendance, namely the number of activities attended by employees during the organization's working period, Interpersonal impact, which involves increasing self-esteem, good relations and cooperation between co-workers, as well as with subordinates and superiors.The result shows that the management information system has a significant effect on performance. From the t test in this study shows the value of t count> t table (11.252>2.017) which means that the hypothesis is accepted. A positive t-count means that the effect is positive, that is, if the management information system is good, the performance level will also be good.The test results of the coefficient of determination (R2) show that the R Square value is 0.746 or 74.6%, indicating that the performance variable (Y) can be explained by the management information system variable (X). Furthermore, in the coefficient of determination test results, there is an R value of 0.864 or 86.4% where the correlationcoefficient value shows that the relationship between management information systems and performance is close.